Pengembangan LKPD Terintegrasi Praktikum Berbasis Kontekstual dengan Komponen REACT pada Materi Sistem Koloid untuk Kelas XI SMA/ MA - Rima Jumalia; Suryelita Suryelita (Entalpi Pendidikan Kimia, 2022)
The colloid system is a chemical material that is studied in class XI SMA/ MA in even semester. This material is close to everyday life, especially the nature, example, and requires practicum. Therefore, one of the learning strategies that can be used is contextual. The aim of the research is to produce an integrated LKPD for contextual-based practicum with a REACT component and determine the validity and practicality categories of teaching materials. The type of research is research and development (R&D) with a 4-D model, namely define, design, and develop, while the dissaminate stage is not carried out. The research data were analyzed using the Aiken’s V formula. Based on the analysis of the validity test questionnaire by 3 lecturers and 2 chemistry teachers, it was found that the LKPD was valid (0,86). The results of the analysis of the practicality questionnaire given to 3 chemistry teachers had a very practical category (92,30%) and the results of the questionnaire analysis given to 36 students of class XI had a very practical category (84,40%). Keywords: Colloid System, LKPD, Contextual Strategy, Validity and Practicality